Sex and Adverse Events of Adjuvant Chemotherapy in Colon Cancer: An Analysis of 34 640 Patients in the ACCENT Database. (24th August 2020) - Wagner, Anna D; Grothey, Axel; Andre, Thierry; Dixon, Jesse G; Wolmark, Norman; Haller, Daniel G; Allegra, Carmen J; de Gramont, Aimery; VanCutsem, Eric; Alberts, Steven R; George, Thomas J; O'Connell, Michael J; et al.
Abstract: Background: Adjuvant chemotherapy is a standard treatment option for patients with stage III and high-risk stage II colon cancer. Sex is one of several factors responsible for the wide inter-patient variability in drug responses. Amalgamated data on the effect of sex on the toxicity of current standard adjuvant treatment for colorectal cancer are missing. Methods: The objective of our study was to compare incidence and severity of major toxicities of fluoropyrimidine- (5FU or capecitabine) based adjuvant chemotherapy, with or without oxaliplatin, between male and female patients after curative surgery for colon cancer. Adult patients enrolled in 27 relevant randomized trials included in the ACCENT (Adjuvant Colon Cancer End Points) database, a large, multi-group, international data repository containing individual patient data, were included. Comparisons were conducted using logistic regression models (stratified by study and treatment arm) within each type of adjuvant chemotherapy (5FU, FOLFOX, capecitabine, CAPOX, and FOLFIRI). The following major toxicities were compared (grade III or IV and grade I-IV, according to National Cancer Institute Common Terminology Criteria [NCI-CTC] criteria, regardless of attribution): nausea, vomiting, nausea or vomiting, stomatitis, diarrhea, leukopenia, neutropenia, thrombocytopenia, anemia, and neuropathy (in patients treated with oxaliplatin). Results: Data from 34 640 patients were analyzed. Statistically significant and clinically relevant differences in the occurrence of grade III or IV nonhematological especially nausea (5FU: odds ratio [OR] = 2.33, 95% confidence interval [CI] = 1.90 to 2.87, P < .001; FOLFOX: OR = 2.34, 95% CI = 1.76 to 3.11, P < .001), vomiting (5FU: OR = 2.38, 95% CI = 1.86 to 3.04, P < .001; FOLFOX: OR = 2.00, 95% CI = 1.50 to 2.66, P < .001; CAPOX: OR = 2.32, 95% CI = 1.55 to 3.46, P < .001), and diarrhea (5FU: OR = 1.35, 95% CI = 1.21 to 1.51, P < .001; FOLFOX: OR = 1.60, 95% CI = 1.35 to 1.90, P < .001; FOLFIRI: OR = 1.57, 95% CI = 1.25 to 1.97, P < .001) as well as hematological toxicities (neutropenia [5FU: OR = 1.55, 95% CI = 1.37 to 1.76, P < .001; FOLFOX: OR = 1.96, 95% CI = 1.71 to 2.25, P < .001; FOLFIRI: OR = 2.01, 95% CI = 1.66 to 2.43, P < .001; capecitabine: OR = 4.07, 95% CI = 1.84 to 8.99, P < .001] and leukopenia [5FU: OR = 1.74, 95% CI = 1.40 to 2.17, P < .001; FOLFIRI: OR = 1.75, 95% CI = 1.28 to 2.40, P < .001]) were observed, with women being consistently at increased risk. Conclusions: Our analysis confirms that women with colon cancer receiving adjuvant fluoropyrimidine-based chemotherapy are at increased risk of toxicity. Given the known sex differences in fluoropyrimidine pharmacokinetics, sex-specific dosing of fluoropyrimidines warrants further investigation.